ANALISIS PERAN HEDONIC VALUE DALAM MEMEDIASI PENGARUH ANTICIPATION DAN EXPERIENCE TERHADAP REPEAT PURCHASE INTENTION PRODUK BLOKEES (IMPLEMENTASI STRATEGI UNCERTAINTY MARKETING) - Steven Wijaya; andreas kiky (Jurnal Nusa Manajemen, 2026)
This study aims to analyze the influence of uncertainty marketing strategy through Anticipation and Experience variables on Repeat Purchase Intention, with Hedonic Value acting as a mediating variable among consumers of Blokees blind box toys. The blind box phenomenon, which combines surprise elements with assembly activities (model kits), represents a unique marketing strategy that requires evaluation regarding its effectiveness in building consumer loyalty. This study employs a quantitative approach. Data were collected through a questionnaire survey of 96 respondents who have purchased Blokees products, using a purposive sampling technique. Hypothesis testing was conducted using path analysis assisted by SPSS software and PROCESS Macro by Hayes. The results indicate that Anticipation has a positive and significant effect on Hedonic Value. Furthermore, Hedonic Value is proven to fully mediate the relationship between Anticipation and Repeat Purchase Intention. Conversely, the Experience variable (assembly activity) was found to have no significant effect on Repeat Purchase Intention. This finding suggests that for the predominantly novice consumer base, the complexity of the assembly process has not yet fostered sufficient competence to drive loyalty. The study concludes that the primary driver of repeat purchase intention is the curiosity regarding the mysterious contents, rather than the technical assembly experience. Managerial implications suggest that marketers should focus more on promoting the mystery element and simplifying the assembly process.